Immobilization techniques applied to the development of biocatalysts for the synthesis of nucleoside analogue derivatives - Trelles, Jorge Abel (2017)
Abstract: Background: Nucleoside analogue (NAs) derivatives comprise a large family of pharmaceuticals clinically used as antitumoral and antiviral compounds. Originally, the production of NAs involved chemical synthesis, but a greener bioproduction alternative exists and involves the use of enzymes that catalyze transglycosylation reactions between modified purinic or pyrimidinic bases and sugars. To be considered as an option for industrial application, it is vital to immobilize these biocatalysts. Methods: This article describes current methodologies for whole cell and protein immobilization mostly applied to the synthesis of important NAs. Immobilization describes ways of cell or enzyme confinement in diverse surfaces or matrixes. It is important to be familiar with the variety of matrixes and supports available prior to biocatalyst immobilization so the most adequate can be selected for the purpose sought. Results: From the different articles compiled, it can be acknowledged that the main methods for protein or cell stabilization are immobilization by adsorption, covalent, cross-linking and entrapment. The most widely used matrixes and supports are agar, alginate, polyacrylamide, sepharose derivatives, and acrylic resins, among others. Protein or cell stabilization has the advantage of stabilizing immobilization, favoring their facile separation from the reaction medium for further reuse and also making the purification of the final product easier. Moreover, biocatalyst stabilization allows a facile estimation of the economic cost of the bioprocess and of an eventual scale-up, being a basic requirement for industrial application. Conclusion: In order to achieve successful biocatalyst immobilization, parameters such as biocatalyst stability,mechanical resistance, and reusability should be considered. This review describes and summarizes the methods used for the immobilization of biocatalysts for the synthesis of NAs in the last years.